Kajian Rujukan Tampilan Antarmuka Aplikasi E-Commerce Untuk Lansia - Fanicia Meilian; Egi Anwari (Universitas Multimedia Nusantara, 2022)
The pace of technology development could not be followed properly by all age groups in society, one in particular, the older adult group. As a matter of fact, the existence of technological developments has the potential to improve the quality of life of older adults, one of which is the convenience of e-commerce. Unfortunately, in the use of technology, many older adults do not feel competent to deal with technology. In this paper, data are analyzed and collected using qualitative methods to explore the experiences of old age users regarding the interface of e-commerce applications. The results were implemented into the reference of the interface design element that was tailored to the experience of older users, which has not been specifically discussed by other research projects. The findings expected to increase the effectiveness of e-commerce application design aimed at older users. Keywords: interface; older adults; e-commerce; design references